Information Ownership and Privacy Control in Information Society - Lucky Stephen, Godwin; Mgbodichima Jummai, Nwabugwu (International Journal of Scientific Research and Management (IJSRM), 2022)
Information ownership and privacy control of information are two inter-related aspects of privacy protection that have emerged as essential areas of study for academics, information scientists, businesses, lawyers, and policymakers with the advance of information technology in the information society. Information ownership and privacy control is an essential area of focus in today’s digital world and modern information society where information can so easily be captured, stored, and shared. Multidisciplinary privacy research has been conducted for decades. Yet, information ownership and privacy control remains a complicated subject that still provides fertile ground for further investigation, especially in the modern information society. This paper, therefore, discusses the concept and characteristics of information ownership, information privacy control, and information ownership & privacy control in the information society.